A Novel method for the simultaneous identification of methylcytosine and hydroxymethylcytosine at a single base resolution. Issue 4 (24th October 2016) - Kawasaki, Yuki; Kuroda, Yukiko; Suetake, Isao; Tajima, Shoji; Ishino, Fumitoshi; Kohda, Takashi
Abstract: Since the discovery of oxidative demethylation of methylcytosine (mC) by Tet enzymes, an analytical method has been urgently needed that would enable the identification of mC and hydroxymethylcytosine (hmC) at the single base resolution level, because their roles in gene regulation are quite different from each other. However, the bisulfite sequencing method, the gold standard for DNA methylation analysis at present, does not distinguish them. Recently reported alternative methods, such as oxBS-seq and TAB-seq, are not even capable of determining mC and hmC simultaneously. Here, we report a novel method for the direct identification of mC, hmC and unmodified cytosine (C) at a single base resolution. We named this method the Enzyme-assisted Identification of Genome Modification Assay (EnIGMA), and it was demonstrated to indeed have a highly efficient and reliable analytic capacity for distinguishing them. We also successfully applied this novel method to the analysis of the maintenance of the DNA methylation status of imprinted H19-DMR. Importantly, hydroxymethylation plays an ambivalent role in the maintenance of the genome imprinting memory in parental genomes essential for normal development, shedding new light on the epigenetic regulation in ES cells.